ANALYSIS OF CUSTOMER SATISFACTION AND LOYALTY OF COFFEE SHOP KOPLO IN NORTH JAKARTA - Akhmad Riyadi Wastra; Junaidi Junaidi; Jannisah Dwi Rahhadiski (AGRIBUSINESS JOURNAL, 2020)
The occurrence of changes in people's lifestyles toward coffee drinking culture has caused the development of the coffee shop industry to be higher, which has an impact on the number of consumers. The key to successful loyalty lies in the consistentness of maintaining market share, and a continuous commitment to increasing consumer satisfaction by maintaining quality and innovation to maintain competitive superiority.The data used in this study was pyramid was obtained through the results of filling out questionnaires and interviews about Coffee shop KopLo. Secondary data obtained from literature reviews. The methods used in this study areBrand Loyalty analysis, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA) which are processed with Microsoft Excel 2013 and SPSS 20.The variables used in this study were the 7P marketing mix.Based on the results of the study, it was obtained that the consumers who visited the most were respondents who were domiciled in the city of North Jakarta, male gender, with an average age of 21-30 having the last undergraduate education, the status of married, namely unmarried, the type of work is a private employee, and the average income per month is Rp. 2,500,001 - Rp. 5,000,000. The attributes that must be maintained are attributes in quadrant II (taste, quality, and taste, aroma, products to order, price list, location, waiter's anxiety, and waiter's explanation). The attributes that must be improved are the attributes in quadrant I (type, discount, promotion through Instagram, and the atmosphere of the place). Then for measurements regarding consumer satisfaction with coffee shop KopLo attributes, it is found that in general consumers have been satisfied with coffee shop KopLo services and products. Coffee shop KopLo loyalty conditions are quite good. Coffee shop KopLo consumers can be said to be quite loyal because most consumers (50%) have recommended to others to buy at Coffee shop KopLo.